UJI AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK DAUN SIRIH DAN BIJI PINANG SERTA GAMBIR TERHADAP Streptococcus mutans - Munira Munira; Galuh Trioktafiani; Muhammad Nasir (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Chewing the betel leaf is a proses of concocting a mixture of several ingredients such us betel leaves, areca nuts and gambier were known to provide a refreshing teste, overcoming stress and believed can strengthen teeth and gums. In addition, these plants also suspected of having antibacterial potential. This research was conducted to determine the ability of combination of betel leaf extract, areca nut and gambier against Streptococcus mutans. This research was experimental by using Completely Randomized Design (CRD) with 8 treatments which is P0 (aquadest), P1combination of betel leaf extract, areca nut and gambier (3:3:3), P2 (3:2:3), P3 (3:1:2), P4 (1:2:3), P5 (2:1:3). P6 (1:3:2) dan P7 (2:3:1). Microbiology test using was diffusion method. Based on results of Anova showed that combination of betel leaf extract, areca nut and gambier greatly effect the growth of Streptococcus mutans (P = 0,000). Duncan further test results showed that the largest average diameter of inhibition zone is indicated by P1 which is 29,50 mm and not significantly different from P2 (26,0 mm) and P3 (26,25 mm) but significantly different from P4 (18,25 mm), P5 (21,5 mm), P6 (18,75 mm) and P7 (21,75 mm). While the smallest average diameter of inhibition zone is indicated by P4 (18,24 mm) and not significantly different from P5 (21,50 mm), P6 (18,75 mm) and P7 (21,75 mm) but significantly different from P1 (29,50 mm) and not significantly different from P2 (26,0 mm) and P3 (26,25 mm).